CARA SUKSES DUNIA DAN AKHIRAT UNTUK GENERASI MILENIAL DI ERA DIGITAL - Kuswandi Kuswandi; Dadang Surya Kancana; Ali Satri Efendi; Tri Winarto (POLITEKNIK LP3I JAKARTA, 2022)
Millennials were born by the digital era where technology has become an inseparable part of their lives. This has become an impetus for many companies to also switch to the digital realm. The Millennial Generation spends time communicating via the internet or smart phones and social media, while the previous generation prefers to communicate face-to-face. However, instead of using technology appropriately, many Millennials use various platforms for unnecessary things, such as excessive surfing on the internet, focusing on various hoaxes on social media, to inappropriate self-actualization. The digital era has also made the current generation lose focus on religious values. Efforts to overcome the problems of the Millennial Generation in achieving success in this world and the hereafter are socialization of the importance of developing various Millennial characteristics, including having a realistic vision of the future, rich in innovative ideas, smart in managing finances, being confident and opening up to new insights.Keywords: Digital Era, Millennials, Success, Generation.